A Cross-Sectional Study on the Level of Knowledge, Attitude and Practice in Fire Extinguisher Management Among Prime Mover Operators in a Container Port - Mesran, Nurul Izzah; Sahak, Nurrul Hafeezah; Holid, Mohd Bohari (Progress in Engineering Application and Technology, 2024)
The high possibility of prime mover accident involving fire to be happen could create an immediate hazard and greater consequences in a container port. Thereafter, the fire extinguisher that was placed in every prime mover is indeed considered essential safety equipment and a critical tool for fire prevention and control. An effective fire extinguisher management was also essential to ensure their effectiveness in case of emergency. This study evaluated the level of knowledge, attitude, and practice in fire extinguisher management among prime mover operators in a container port. This is part of a bigger study on level of KAP in fire extinguisher management among prime mover operators in a container port. For data collection, this study adopted quantitative research which constructed a questionnaire survey. In addition, all data were examined and evaluated by using Statistical Package for the Social Sciences (SPSS) version 29. By using the SPSS software, it was proved that the level of knowledge in fire extinguisher management among prime mover operators was negative or by other words was low while fore the level of attitude was highly positive. The level of practice in fire extinguisher management among prime mover operators in container port was excellent.